Wear-resistant coating and preparation method thereof
By regulating the proportion of sp2 phase of carbon in the functional layer of the wear-resistant coating and preparing it in combination with the electrodeposition method, the problem of reducing the wear-resistant effect of the existing wear-resistant coating after the number of frictions is increased, and the high bonding strength and long wear-resistant life of the coating are achieved.
Patent Information
- Application Number
- CN202411684122.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-04
AI Technical Summary
Under the influence of external factors, the wear-resistant coating has significantly reduced the wear-resistant effect after the number of frictions increases, and even falls off, and has a short service life.
Carbon material is used as the functional layer, and the sp2 phase ratio of carbon is adjusted to continuously or gradiently change along the thickness direction by regulating the coating, and the mass content of sp2 phase elemental carbon in the functional layer is adjusted.
It achieves good bonding strength and long wear-resistant life of the coating, can withstand various external forces, and meets the wear-resistant coating setting index requirements of mechanical structures.
Smart Images

Figure BDA0005149032290000131 
Figure BDA0005149032290000132 
Figure BDA0005149032290000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a wear-resistant coating and a preparation method thereof. Background Art
[0002] Mechanical structures need to face friction losses during connection, transmission, and braking, so wear-resistant coatings are generally applied on the surface. Currently, common wear-resistant coatings are based on lightness and wear resistance, and basically use diamond-like materials as the main material. In addition, according to the actual application field, doping, lamination, and other methods are used to optimize the use effect. This type of wear-resistant coating has good wear resistance at the initial stage of installation. However, under the influence of external factors, as the number of frictions increases, the wear resistance of the coating is reduced, and even part of the coating falls off. The wear resistance drops drastically, and the scope of coating installation is greatly limited. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of the present invention is to provide a wear-resistant coating, which uses carbon material as a functional layer, and at the same time sets the sp2 phase ratio of carbon in the functional layer to change continuously or gradiently along the thickness direction. It not only has good coating bonding strength, but also has a long wear-resistant life, can withstand external forces under various conditions, and meet the requirements for setting indicators of wear-resistant coatings of various mechanical structures.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A wear-resistant coating comprises a base layer and a functional layer;
[0006] The functional layer includes elemental carbon, and the elemental carbon includes sp2 phase elemental carbon;
[0007] The functional layer includes a first surface and a second surface along the thickness direction, and the mass content of the sp2 phase elemental carbon in the elemental carbon increases continuously or gradually from the first surface to the second surface;
[0008] The mass content of sp2 phase elemental carbon in the elemental carbon on the second surface is ≥30%.
[0009] In a second aspect of the present invention, the present invention also provides a method for preparing a wear-resistant coating, comprising the following steps:
[0010] (1) Setting a base layer;
[0011] (2) providing a functional layer containing elemental carbon by electrodeposition;
[0012] When the functional layer is provided, the mass content of the sp2 phase elemental carbon in the functional layer is adjusted by regulating the electrodeposition bias voltage and the current.
[0013] The beneficial effect of the present invention is that the present invention provides a wear-resistant coating, which uses carbon material as a functional layer, and at the same time sets the sp2 phase ratio of carbon in the functional layer to change continuously or gradiently along the thickness direction. It not only has good coating bonding strength, but also has a long wear-resistant life, can withstand external forces under various conditions, and meet the index requirements for setting wear-resistant coatings of various mechanical structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a scanning electron microscope image of the wear-resistant coating obtained in Example 1 of the present invention.
[0015] Figure 2 This is a graph showing the interlayer bonding strength test results of the wear-resistant coating obtained in Example 1 of the present invention.
[0016] Figure 3 This is a scanning electron microscope image of the wear-resistant coating obtained in Example 1 of the present invention after the wear-resistant life test.
[0017] Figure 4 This is a scanning electron microscope image of the wear-resistant coating obtained in Example 2 of the present invention.
[0018] Figure 5 This is a graph showing the interlayer bonding strength test results of the wear-resistant coating obtained in Example 2 of the present invention.
[0019] Figure 6 This is a graph showing the interlayer bonding strength test results of the wear-resistant coating obtained in Example 3 of the present invention.
[0020] Figure 7 This is a scanning electron microscope image of the wear-resistant coating obtained in Example 6 of the present invention.
[0021] Figure 8 This is a graph showing the interlayer bonding strength test results of the wear-resistant coating obtained in Example 6 of the present invention.
[0022] Fig. 9 This is a scanning electron microscope image of the wear-resistant coating obtained in Example 6 of the present invention after the wear-resistant life test.
[0023] Fig.10 This is a graph showing the interlayer bonding strength test results of the wear-resistant coating obtained in Comparative Example 1 of the present invention.
[0024] Fig.11 This is a scanning electron microscope image of the wear-resistant coating obtained in Comparative Example 1 of the present invention after the wear-resistant life test.
[0025] Fig.12 This is a scanning electron microscope image of the wear-resistant coating obtained in Comparative Example 2 of the present invention.
[0026] Fig.13This is a graph showing the interlayer bonding strength test results of the wear-resistant coating obtained in Comparative Example 2 of the present invention.
[0027] Fig.14 This is a scanning electron microscope image of the wear-resistant coating obtained in Comparative Example 3 of the present invention.
[0028] Fig.15 This is a graph showing the interlayer bonding strength test results of the wear-resistant coating obtained in Comparative Example 3 of the present invention.
[0029] Fig.16 This is a scanning electron microscope image of the wear-resistant coating obtained in Comparative Example 3 of the present invention after the wear-resistant life test.
[0030] Fig.17 This is a scanning electron microscope image of the wear-resistant coating obtained in Comparative Example 4 of the present invention.
[0031] Fig.18 This is a graph showing the interlayer bonding strength test results of the wear-resistant coating obtained in Comparative Example 4 of the present invention.
[0032] Fig.19 This is a scanning electron microscope image of the wear-resistant coating obtained in Comparative Example 4 of the present invention after the wear-resistant life test. DETAILED DESCRIPTION
[0033] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0034] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0035] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0036] The present invention is further described below with specific embodiments:
[0037] A wear-resistant coating comprises a base layer and a functional layer;
[0038] The functional layer includes elemental carbon, and the elemental carbon includes sp2 phase elemental carbon;
[0039] The functional layer includes a first surface and a second surface along the thickness direction, and the mass content of the sp2 phase elemental carbon in the elemental carbon increases continuously or gradually from the first surface to the second surface;
[0040] The mass content of sp2 phase elemental carbon in the elemental carbon on the second surface is ≥30%.
[0041] In some embodiments, the mass content of sp2 phase elemental carbon in the elemental carbon on the first surface is ≥ 20%;
[0042] In some embodiments, the mass content of sp2 phase elemental carbon in the elemental carbon on the second surface is ≤40%.
[0043] In the prior art, the sp3 phase content of carbon materials in the wear-resistant coating set with diamond-like materials is extremely high (can reach more than 90%), and the coating shows excellent initial hardness and corrosion resistance. In theory, it should have an ideal wear-resistant effect. However, in the actual operation process, the inventors found that this product is prone to high temperature after being subjected to external friction. If the influence of external factors is added, the bonding strength between the coating and the substrate will be greatly reduced, which is not conducive to the long-term use of the coating. Even if anti-friction lubricants or coolants are further introduced, the effect of extending the service life of the coating is very limited. The inventors have found through experiments that when carbon is used as a functional layer component of the wear-resistant coating, the difference in properties between the sp2 phase and the sp3 phase in the carbon element will directly affect the hardness, bonding strength and structural stability of the coating itself, thereby affecting its use effect and service life during use. Among them, the sp3 phase elemental carbon will improve the hardness and corrosion resistance of the product, while the sp2 phase elemental carbon can improve the self-lubricating property of the product. The wear-resistant coating developed by the present invention uses elemental carbon as a functional layer component, and at the same time, the mass content of the sp2 phase elemental carbon in the functional layer along the thickness direction is set to change in a gradient or continuous manner, so that at the bottom of the functional layer ( That is, the first surface) has a relatively small content of sp2 phase carbon in the carbon, and its content increases along the thickness direction to the surface of the functional layer (the second surface). The self-lubricating effect of the sp2 phase carbon reduces the influence of external forces on the stability of the coating structure, and avoids the rapid accumulation of heat generated by friction. At the same time, it does not reduce the mechanical strength of the functional layer itself and the bonding strength with the base layer. Compared with existing products, the overall wear-resistant coating not only has an ideal initial effect, but also maintains a high stability after multiple external forces and changes in external conditions, has a long service life, and meets the requirements for wear-resistant coatings on various mechanical structures.
[0044] In some embodiments, the functional layer is elemental carbon.
[0045] In some embodiments, the elemental carbon is sp2 phase elemental carbon and sp3 phase elemental carbon.
[0046] In some embodiments, the sum of the mass contents of the sp2 phase elemental carbon and the sp3 phase elemental carbon is 100%.
[0047] In some embodiments, the mass content of sp2 phase elemental carbon and sp3 phase elemental carbon in the elemental carbon in the thickness direction of the functional layer is tested by XPS etching method, and the specific characteristic spectrum collected is C1s core-loss, and the energy range of the spectrum is E=280~320eV.
[0048] In some embodiments, the thickness of the functional layer is 1 to 5 μm.
[0049] For example, in some embodiments, the thickness of the functional layer is in the range of one or any two of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm.
[0050] In some embodiments, the first surface of the functional layer is adjacent to the base layer.
[0051] In some embodiments, the mass content of sp2 phase elemental carbon in the elemental carbon increases continuously from the first surface to the second surface.
[0052] In some embodiments, the mass content of sp2 phase elemental carbon in the elemental carbon increases gradually from the first surface to the second surface.
[0053] It should be noted that the mass content of sp2 phase elemental carbon in the elemental carbon described in the present invention can be set to a continuously increasing distribution in the direction from the first surface to the second surface, that is, as the thickness direction moves from the first surface to the second surface, the mass content of sp2 phase elemental carbon in the elemental carbon in the planar layer continuously increases with increasing thickness, thereby taking into account the joint action of sp2 phase elemental carbon and sp2 phase elemental carbon within a limited range. It can also be set to a gradient increasing distribution in the direction from the first surface to the second surface. For example, it is further divided into several structural layers in the direction from the first surface to the second surface, and the mass content of sp2 phase elemental carbon in each layer is constant, but the mass content of sp2 phase elemental carbon in the structural layer adjacent to the first surface is greater than the mass content of sp2 phase elemental carbon in the structural layer away from the first surface.
[0054] For example, in some embodiments, when the functional layer is tested by the XPS etching method, XPS etching is performed starting from the second surface, and when the etching depth reaches 10% to 30% of the thickness of the functional layer, the mass content of the sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 35 to 40%, and when the etching depth reaches 30 to 60% of the thickness of the functional layer, the mass content of the sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 25 to 35%, and when the etching depth reaches more than 60% of the thickness of the functional layer, the mass content of the sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 20 to 25%.
[0055] Specifically, in some embodiments, when the functional layer is tested by the XPS etching method, XPS etching is performed starting from the second surface, and when the etching depth reaches 10% to 20% of the thickness of the functional layer, the mass content of sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 39% to 40%, and when the etching depth reaches 20% to 40% of the thickness of the functional layer, the mass content of sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 36% to 38%, and when the etching depth reaches 30% to 60% of the thickness of the functional layer, the mass content of sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 32% to 34%, and when When the depth reaches 40-70% of the thickness of the functional layer, the mass content of sp2 phase carbon in the carbon on the etching plane of the functional layer is 30-32%; when the etching depth reaches 60-80% of the thickness of the functional layer, the mass content of sp2 phase carbon in the carbon on the etching plane of the functional layer is 27-29%; when the etching depth reaches 80-90% of the thickness of the functional layer, the mass content of sp2 phase carbon in the carbon on the etching plane of the functional layer is 23-24%; when the etching depth reaches more than 80% of the thickness of the functional layer, the mass content of sp2 phase carbon in the carbon on the etching plane of the functional layer is 20-21%.
[0056] Specifically, in some embodiments, when the functional layer is tested by the XPS etching method, XPS etching is performed starting from the second surface, and when the etching depth reaches 10% to 20% of the thickness of the functional layer, the mass content of sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 40%; when the etching depth reaches 20% to 40% of the thickness of the functional layer, the mass content of sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 37%; when the etching depth reaches 30% to 60% of the thickness of the functional layer, the mass content of sp2 phase elemental carbon in the elemental carbon on the etched plane of the functional layer is 33%; When the etching depth reaches 40-70% of the thickness of the functional layer, the mass content of sp2 phase carbon in the carbon on the etching plane of the functional layer is 31%; when the etching depth reaches 60-80% of the thickness of the functional layer, the mass content of sp2 phase carbon in the carbon on the etching plane of the functional layer is 28%; when the etching depth reaches 80-90% of the thickness of the functional layer, the mass content of sp2 phase carbon in the carbon on the etching plane of the functional layer is 24%; when the etching depth reaches more than 80% of the thickness of the functional layer, the mass content of sp2 phase carbon in the carbon on the etching plane of the functional layer is 20%.
[0057] For example, in some embodiments, the functional layer includes n structural layers in sequence from the first surface to the second surface, the structural layer adjacent to the first surface is the first structural layer, and the structural layer adjacent to the second surface is the nth structural layer, n≥3 and is a positive integer; the mass content of sp2 phase elemental carbon in each structural layer is constant;
[0058] The mass of the sp2 phase single carbon of the single carbon in the nth structural layer is greater than the mass of the sp2 phase single carbon of the single carbon in the n-1th structural layer.
[0059] For example, in some embodiments, the functional layer includes a first structural layer, a second structural layer and a third structural layer in sequence from the first surface to the second surface; the mass content of sp2 phase elemental carbon in each structural layer is constant.
[0060] In some embodiments, the mass content of sp2 phase single carbon in the first structural layer is a%; the mass content of sp2 phase single carbon in the second structural layer is b%; the mass content of sp2 phase single carbon in the third structural layer is c%;
[0061] Among them, 20≤a≤25, 25<b≤35, 35<c≤40.
[0062] By setting up at least three gradient structure layers, the carbon close to the surface of the functional layer can be guaranteed to give full play to the self-lubricating effect of the sp2 phase and improve its wear resistance life. The carbon in the bottom layer can take into account the bonding strength with the adjacent layers based on the sp3 phase, and the film-forming effect of the functional layer is ensured through the interlayer design.
[0063] In some embodiments, the thickness ratio of the first structure layer, the second structure layer, and the third structure layer is (6.5-7.5): (1.5-2.5): (0.5-1.5).
[0064] For example, in some embodiments, the thickness ratio of the first structure layer, the second structure layer, and the third structure layer is in the range of one or any two of 7:2:1, 6.5:2.5:1, 7.5:1.5:1, 7:1.5:1.5, 7:2.5:0.5, 6.5:2:1.5, and 7.5:2:0.5.
[0065] For example, in some embodiments, the ratio of the thickness of the first structure layer, the second structure layer, and the third structure layer is (3.5-4.5): (3.5-4.5): (1.5-2.5).
[0066] In some embodiments, the ratio of the thickness of the first structure layer, the second structure layer, and the third structure layer is (3.5-4.5): (2.5-3.5): (2.5-3.5).
[0067] Those skilled in the art can select a suitable structural layer thickness setting according to actual requirements. Under the setting of the continuous or gradient sp2 phase elemental carbon content described in the present invention, each thickness can achieve the expected effect.
[0068] For example, in some embodiments, the functional layer includes a first structural layer, a second structural layer, a third structural layer, a fourth structural layer, a fifth structural layer, a sixth structural layer, and a seventh structural layer in sequence from the first surface to the second surface; the mass content of sp2 phase elemental carbon in each structural layer is constant.
[0069] The mass content of sp2 phase of single carbon in the first structural layer is a'%; the mass content of sp2 phase of single carbon in the second structural layer is b'%; the mass content of sp2 phase of single carbon in the third structural layer is c'%; the mass content of sp2 phase of single carbon in the fourth structural layer is d'%; the mass content of sp2 phase of single carbon in the fifth structural layer is e'%; the mass content of sp2 phase of single carbon in the sixth structural layer is f'%; the mass content of sp2 phase of single carbon in the seventh structural layer is g'%;
[0070] Among them, a'=20, 20<b'≤24, 24<c'≤28, 28<d'≤31, 31<e'≤33, 33<f'≤37, 37<g'≤40.
[0071] In addition, it should be noted that the structural layer design within the functional layer described in the present application is not limited to the above-mentioned specific implementation methods. As mentioned above, the technical effect of the wear-resistant coating described in the present application is mainly based on the functional layer formed by gradient or continuously changing elemental carbon. Without changing the characteristics of the elemental carbon, technical personnel in this field can design different numbers of structural layers according to actual needs.
[0072] In some embodiments, a primer layer is further provided between the base layer and the functional layer.
[0073] In some embodiments, the primer layer is a metal layer.
[0074] In some embodiments, the primer layer is any one of a pure metal layer, a metal alloy layer, a doped metal layer, a metal carbide layer, and a metal nitride layer.
[0075] For example, in some embodiments, the metal element in the primer layer includes at least one of tantalum, niobium, chromium, titanium, tungsten, and nickel.
[0076] The design of the base layer on the base layer can effectively protect the base layer when the functional layer is prepared, and can also further improve the interlayer bonding strength of the overall wear-resistant coating. At the same time, based on the design of the functional layer described in this application, the bonding strength between the base layer arranged in the middle part and the base layer is higher than that of the conventional interlayer design product, and the effect is better. In addition, those skilled in the art can select the base layer according to actual requirements and production conditions, for example, based on cost considerations, select a titanium single substance layer with a lower cost as the base layer, or based on anti-corrosion considerations, select a metal alloy layer as the base layer.
[0077] In some embodiments, the thickness of the primer layer is 50 to 1500 nm.
[0078] For example, in some embodiments, the thickness of the primer layer is in the range of one or any two of 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 800 nm, 1000 nm, 1200 nm, 1250 nm, 1400 nm, and 1500 nm.
[0079] In some embodiments, the base layer is composed of at least one of a metal alloy, a steel material, and an alloy steel.
[0080] In some embodiments, the Vickers hardness of the wear-resistant coating (load 1 kgf, loading time 10 s) is 1130-1300 HV.
[0081] It should be noted that the wear-resistant coating of the present invention can be directly prepared by existing conventional process techniques, for example, after setting the base layer and the base layer, it can be prepared by chemical vapor deposition, physical vapor deposition, or magnetron sputtering. That is, the wear-resistant coating is not limited to the following preparation method.
[0082] A method for preparing a wear-resistant coating comprises the following steps:
[0083] (1) Setting a base layer;
[0084] (2) providing a functional layer containing elemental carbon by electrodeposition;
[0085] When the functional layer is provided, the mass content of the sp2 phase elemental carbon in the functional layer is adjusted by regulating the electrodeposition bias voltage and the current.
[0086] The technical solution of the present invention provides a method for preparing a wear-resistant coating. When constructing the key functional layer of the product, the method is carried out by electrodeposition, and the mass content of the sp2 phase elemental carbon in the deposited elemental carbon is regulated by adjusting the bias voltage and current during electrodeposition. Not only will hydrogen-containing impurities not be introduced, but the mass content of the sp2 phase elemental carbon can also be accurately changed.
[0087] In some embodiments, the thickness of the functional layer is adjusted by the time of electrodeposition.
[0088] Those skilled in the art can adjust the time of each stage of the electrodeposition method according to the specific structural layer design thickness and total thickness of the predetermined functional layer. Within a certain range, the deposition time of each stage is proportional to the thickness of the structural layer in the functional layer deposited in that stage.
[0089] In some embodiments, the electrodeposition method is transition cathode multi-arc electrodeposition (FCVA).
[0090] In some embodiments, the bias voltage is set to 100-1500V;
[0091] In some implementations, when the bias voltage is set ≤ 1000 V, the current is set to 45-125 A; when the bias voltage is set > 1000 V, the current is set to 32-45 A.
[0092] In some embodiments, the electrodeposition method is used to form a functional layer in several stages.
[0093] For example, in some embodiments, including a first stage, a second stage, and a third stage;
[0094] The bias voltage in the first stage is set to 100-500V, the bias voltage in the second stage is set to 500-1250V, and the bias voltage in the third stage is set to 1350-1500V.
[0095] Correspondingly, the functional layer of the present invention can adjust the electrodeposition time of several stages accordingly based on the setting of the above-mentioned structural layer. For example, in some embodiments, the ratio of the electrodeposition time of the first stage, the second stage, and the third stage is (6.5~7.5): (1.5~2.5): (0.5~1.5).
[0096] For example, in some embodiments, the ratio of the electrodeposition time of the first stage, the second stage, and the third stage is in the range of one or any two of 7:2:1, 6.5:2.5:1, 7.5:1.5:1, 7:1.5:1.5, 7:2.5:0.5, 6.5:2:1.5, and 7.5:2:0.5.
[0097] For example, in some embodiments, the ratio of the electrodeposition time of the first stage, the second stage, and the third stage is (3.5-4.5): (3.5-4.5): (1.5-2.5).
[0098] In some embodiments, the ratio of the electrodeposition time of the first stage, the second stage, and the third stage is (3.5-4.5): (2.5-3.5): (2.5-3.5).
[0099] In some embodiments, the method comprises the first to seventh stages;
[0100] The bias voltage in the first stage is set to 100-210V, the bias voltage in the second stage is set to 150-450V, the bias voltage in the third stage is set to 300-500V, the bias voltage in the fourth stage is set to 450-850V, the bias voltage in the fifth stage is set to 850-1100V, the bias voltage in the sixth stage is set to 1100-1400V, and the bias voltage in the seventh stage is set to 1350-1500V.
[0101] By setting different bias voltages and currents, the functional layer is divided into several stages during the electrodeposition setting. Under different bias voltage and current settings, the mass content of sp2 phase elemental carbon in the deposited structural layer in each stage presents a gradient form, thereby achieving an excellent effect of both hardness and wear resistance life.
[0102] For example, in some embodiments, the ratio of the deposition time of the first to seventh stages is (1-2):(1-2):(1-2):(1-2):(1-2):(1-2):(1-2):(1-2).
[0103] In some embodiments, the target material used in the electrodeposition method is a graphite target material, the purity of the graphite target material is ≥5N, and the graphite particle size is 4 to 15 μm.
[0104] In some embodiments, the power source used in the electrodeposition method is any one of a direct current power source and a pulse power source.
[0105] In some embodiments, a primer layer is further disposed on the base layer.
[0106] In some implementation methods, the primer layer is provided by any one of physical vapor deposition and transition cathode multi-arc ion electrodeposition.
[0107] In some embodiments, the primer layer is deposited by a transition cathode multi-arc ion electrodeposition method, with the bias voltage set to 100-450V and the current set to 110-160A.
[0108] In some embodiments, when the base layer is provided by a transition cathode multi-arc ion electrodeposition method, the target material used is at least one of a metal element, a metal carbide, and a metal nitride.
[0109] The present invention also provides a mechanical component, the surface of the mechanical component or the connecting piece is provided with the wear-resistant coating of the present invention or the wear-resistant coating prepared by the preparation method.
[0110] The wear-resistant coating of the present invention is based on the phase composition of elemental carbon in the functional layer, which not only effectively solves the defect that the existing common diamond-like coating generates heat due to external force and weakens the wear-resistant life, but also has a long wear-resistant service life, and at the same time has a high initial hardness and fully meets the use indicators.
[0111] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:
[0112] Unless otherwise specified, all examples and comparative examples are commercially available products.
[0113] Example 1
[0114] An embodiment of a wear-resistant coating and a preparation method thereof according to the present invention, the preparation method of the wear-resistant coating comprises the following steps:
[0115] (1) An M42 high-speed steel substrate layer was provided. Before use, the substrate layer was ultrasonically cleaned in water at 50-55° C. for 30 min, then soaked in dilute sulfuric acid for 30 min, finally washed, rinsed with ethanol, plasma cleaned, vacuum dried, and bombarded with argon plasma at 1000 V and 20 sccm flow rate for 700 s to remove the oxide layer.
[0116] (2) a chromium nitride base layer is formed on the substrate layer by using a transition cathode multi-arc ion electrodeposition method, with the bias voltage set to 150 V, the current set to 160 A, and the base layer thickness set to 1000 nm;
[0117] (3) A functional layer is formed on the base layer by a transition cathode multi-arc ion electrodeposition method, a graphite target material, the purity of the graphite target material is 5N, the graphite particle size is 4-15 μm, and a DC power supply is used; the electrodeposition process is set to three stages, respectively constructing the first structural layer, the second structural layer and the third structural layer in the functional layer, wherein the process conditions used in the construction stage and the specific parameters of the obtained functional layer are shown in Tables 1 and 2; the calibrated deposition rate during deposition is 100 nm / 1200 s, and the processing device is calibrated according to the situation when performing 30 to 40 depositions.
[0118] Embodiments 2 to 4
[0119] An embodiment of a wear-resistant coating and a preparation method thereof described in the present invention differs from Embodiment 1 only in that the parameters for setting the functional layer and the parameters for setting the functional layer are different, as shown in Tables 1 and 2. In addition, the thickness of the base layer in Embodiment 4 is 700 nm.
[0120] Example 5
[0121] An embodiment of a wear-resistant coating and a preparation method thereof according to the present invention, the preparation method of the wear-resistant coating comprises the following steps:
[0122] (1) An M42 high-speed steel substrate layer was provided. Before use, the substrate layer was ultrasonically cleaned in water at 50-55° C. for 30 min, then soaked in dilute sulfuric acid for 30 min, finally washed, rinsed with ethanol, plasma cleaned, vacuum dried, and bombarded with argon plasma at 1000 V and 20 sccm flow rate for 700 s to remove the oxide layer.
[0123] (2) a chromium nitride base layer was deposited on the substrate layer by using a transition cathode multi-arc ion electrodeposition method, with the bias voltage set to 210 V, the current set to 1550 A, and the base layer thickness set to 1500 nm;
[0124] (3) A functional layer is formed on the base layer by using a transition cathode multi-arc ion electrodeposition method, a graphite target material, the purity of the graphite target material is 5N, the graphite particle size is 4-15 μm, and a DC power supply; the electrodeposition process is set to seven stages, respectively constructing the first structural layer to the seventh structural layer in the functional layer, wherein the process conditions used in the construction stage and the specific parameters of the obtained functional layer are shown in Tables 3 and 4; the calibrated deposition rate during deposition is 100 nm / 1200 s, and the processing device is calibrated according to the situation when performing 30 to 40 depositions.
[0125] Subsequently, the functional layer of each embodiment was etched at different depths using the XPS etching method to detect the mass content of the sp2 phase. The results are shown in Tables 2 and 4.
[0126] Comparative Example 1
[0127] A wear-resistant coating and a preparation method thereof, which differs from Example 4 only in that the parameters when setting the functional layer and the parameters of the set functional layer are different, as shown in Tables 1 and 2.
[0128] Comparative Example 2
[0129] A wear-resistant coating and a preparation method thereof, the preparation method of the wear-resistant coating comprising the following steps:
[0130] (1) An M42 high-speed steel substrate layer was provided. Before use, the substrate layer was ultrasonically cleaned in water at 50-55° C. for 30 min, then soaked in dilute sulfuric acid for 30 min, finally washed, rinsed with ethanol, plasma cleaned, vacuum dried, and bombarded with argon plasma at 1000 V and 20 sccm flow rate for 700 s to remove the oxide layer.
[0131] (2) a chromium nitride base layer is formed on the substrate layer by using a transition cathode multi-arc ion electrodeposition method, with the bias voltage set to 210 V, the current set to 150 A, and the base layer thickness set to 750 nm;
[0132] (3) A functional layer is set on the base layer by using a transition cathode multi-arc ion electrodeposition method, a graphite target material, the purity of the graphite target material is 5N, the graphite particle size is 4-15 μm, and a DC power supply; the electrodeposition process is set with a bias voltage of 450 V and a current of 60 A, and the bias voltage and current are constant during the electrodeposition process; the calibrated deposition rate during deposition is 100 nm / 1200 s, and the processing device is calibrated according to the situation when performing 30 to 40 depositions.
[0133] Comparative Example 3
[0134] A wear-resistant coating and a preparation method thereof, the preparation method of the wear-resistant coating comprising the following steps:
[0135] (1) An M42 high-speed steel substrate layer was provided. Before use, the substrate layer was ultrasonically cleaned in water at 50-55° C. for 30 min, then soaked in dilute sulfuric acid for 30 min, finally washed, rinsed with ethanol, plasma cleaned, vacuum dried, and bombarded with argon plasma at 1000 V and 20 sccm flow rate for 700 s to remove the oxide layer.
[0136] (2) a first metal chromium base layer and a second chromium nitride base layer are formed on the substrate layer by using a transition cathode multi-arc ion electrodeposition method, wherein the bias voltage when the first metal chromium base layer is formed is set to 210 V, the current is set to 160 A, and the thickness of the first metal chromium base layer is set to 200 nm; the bias voltage when the second chromium nitride base layer is formed is set to 210 V, the current is set to 155 A, and the thickness of the second chromium nitride base layer is set to 350 nm, and the total thickness of the base layers is 550 nm;
[0137] (3) A functional layer is set on the base layer by using a transition cathode multi-arc ion electrodeposition method, a graphite target material, the purity of the graphite target material is 5N, the graphite particle size is 4-15 μm, and a DC power supply; the electrodeposition process is set with a bias voltage of 850 V and a current of 40 A, and the bias voltage and current are constant during the electrodeposition process; the calibrated deposition rate during deposition is 100 nm / 1200 s, and the processing device is calibrated according to the situation when performing 30 to 40 depositions.
[0138] Comparative Example 4
[0139] A wear-resistant coating and a preparation method thereof, the preparation method of the wear-resistant coating comprising the following steps:
[0140] (1) An M42 high-speed steel substrate layer was provided. Before use, the substrate layer was ultrasonically cleaned in water at 50-55° C. for 30 min, then soaked in dilute sulfuric acid for 30 min, finally washed, rinsed with ethanol, plasma cleaned, vacuum dried, and bombarded with argon plasma at 1000 V and 20 sccm flow rate for 700 s to remove the oxide layer.
[0141] (2) a chromium nitride base layer is formed on the substrate layer by using a transition cathode multi-arc ion electrodeposition method, with the bias voltage set to 150 V, the current set to 160 A, and the base layer thickness set to 1400 nm;
[0142] (3) A functional layer is formed on the base layer by a transition cathode multi-arc ion electrodeposition method, a graphite target material, the purity of the graphite target material is 5N, the graphite particle size is 4-15 μm, and a DC power supply is used; the electrodeposition process is set to three stages, respectively constructing the first structural layer and the second structural layer in the functional layer, wherein the process conditions used in the construction stage and the specific parameters of the obtained functional layer are shown in Tables 1 and 2; the calibrated deposition rate during deposition is 100 nm / 1200 s, and the processing device is calibrated according to the situation when performing 30 to 40 depositions.
[0143] Comparative Example 5
[0144] A wear-resistant coating and a preparation method thereof, which differ from Example 1 only in that the parameters when setting the functional layer and the parameters of the set functional layer are different, as shown in Tables 1 and 2.
[0145] Table 1
[0146]
[0147] Table 2
[0148]
[0149]
[0150] Table 3
[0151]
[0152] Table 4
[0153]
[0154]
[0155] Effect Example 1
[0156] In order to verify the effect of each wear-resistant coating, the products obtained from each embodiment and comparative example were subjected to the following tests:
[0157] (1) Scanning electron microscopy morphology observation of wear-resistant coating;
[0158] (2) Vickers hardness test of functional layer (INNOVATEST FALCON 500 Vickers hardness tester, load 1 kg, loading time 10 s);
[0159] (3) The bonding strength between the functional layer and the base layer (micrometer scratch method, using Anton Paar's NHT+MCT coating adhesion automatic scratch tester, scratch length 2 mm, time 1 min, loading rate 30 N / min, during the test, the functional layer is scratched with a scratch tester. If the functional layer and the base layer are damaged during the test, the data will no longer be counted);
[0160] (4) Bonding strength between the primer layer and the base layer (same as step (3); if the functional layer and the primer layer are damaged during the bonding strength test, this step will not be tested);
[0161] (5) Wear life test (multi-scenario accelerated experiment, wear-resistant coating is processed on the friction pair device, the device is placed in a program temperature-controlled environment box, the friction pair is powered on, and it is operated under the set acceleration conditions. The operation scenarios include the following five scenarios: Scenario 1: room temperature, friction pair speed 1200 rpm, 500 h; Scenario 2: -45℃ and 70℃ cycle, friction pair speed 1200 rpm, pre-heating at -45℃ for 2 h, then changing the temperature to 70℃ for 5 min and keeping it for 2 h as one cycle, 250 cycles; Scenario 3: temperature control cycle, friction pair speed 1200 rpm, Change the temperature from 20℃ to -55℃ within 1h and keep it for 2.5h, then change the temperature to 75℃ within 1h and keep it for 1.5h as one cycle, and repeat 100 times; Scenario 4: temperature control cycle, friction pair speed 1200rpm, keep it at -30℃ for 6h in advance, then instantly heat up to 50℃ and keep it for a total of 15h, and finally instantly cool down to 0℃ and keep it for a total of 24h as one cycle, and repeat 50 times; Scenario 5: 45℃, friction pair speed 3000rpm, 500h), observe the functional layer after completion, and calculate whether the acceleration factor meets the normal service life of 10000h.
[0162] The test results are shown in Table 5 and Figures 1 to 3 shown.
[0163] Table 5
[0164]
[0165]
[0166]
[0167] It can be clearly seen from the test results that the size of the wear-resistant coating of the present invention is consistent with expectations, the structure and morphology are uniform, and it has ideal hardness and interlayer bonding strength. Taking Example 1 as an example, Figures 1-2 As shown in the figure, the bonding force between the functional layer and the base layer in the product reaches 16.7N. As the content of sp2 phase elemental carbon in the functional layer gradually increases, the surface lubrication of the wear-resistant coating is improved, which effectively improves the external friction stability of the product under various composite conditions. After high-frequency friction testing, the morphology is basically stable, such as Figure 3 As shown; In addition, Figure 4 and 5 As shown, although the wear resistance of the product in Example 2 is slightly weaker than that in Example 1, it still has an ideal morphology and bonding effect; Figure 6 The bonding strength test results of the product of Example 3 are shown. Compared with the product of Example 2, it is lower, but still can meet the use standard. In addition, the product of Example 6 with multiple structural layers is as follows Figures 7 to 9 As shown in Figure 2, the interlayer bonding strength of this product is high, and the thickness has almost no change after the wear test; in contrast, Figures 10-11 As shown, although the wear-resistant coating in Comparative Example 1 is also designed with a gradient elemental carbon functional layer, the sp2 phase elemental carbon content in the surface layer of the functional layer is relatively small, while the deep layer adjacent to the base layer is large, resulting in not only insufficient service life, but also almost falling off after friction, and the interlayer bonding force is far less than that of the products in the embodiments; Fig.12 As shown, the functional layer in the product of comparative example 2 does not have a gradient structure, and the single carbon with a high sp3 phase content similar to the existing diamond-like wear-resistant coating is used as the functional layer. Although it has a high hardness, the functional layer will fall off seriously under the action of high-frequency external friction and cannot pass the test. Fig.13 As shown, when the interlayer bonding strength is tested, the structural layer is damaged and the service life does not meet the standard; the product of comparative example 3 optimizes the structure of the bottom layer on the basis of the product of comparative example 2, such as Fig.14 As shown in Figure 2, the bonding strength between the functional layer and the base layer is improved. Fig.15 As shown in the figure, there was no overall detachment and failure to complete the test, but after the test, the functional layer was broken and cracked, as shown in the figure. Fig.16 As shown, it also does not have the expected use effect; the product of comparative example 4 is a common two-stage gradient functional layer design, such as Fig.17 As shown, in order to ensure the hardness effect, the sp2 phase carbon content in the single carbon of the overall functional layer is relatively small, while the sp3 phase carbon content is relatively high. Although the interlayer bonding strength is relatively high during the test, Fig.12 As shown, mechanical damage still occurred during the high-frequency friction test, resulting in internal shedding of the functional layer; the product of comparative example 5 is similar to the product of the embodiment, and a gradient functional layer of a similar order is set, but the content of sp2 phase elemental carbon in the overall elemental carbon is relatively low, and the product still has poor performance.
[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A wear-resistant coating, characterized in that: Includes basal layer and functional layer; The functional layer includes elemental carbon, and the elemental carbon includes sp2 phase elemental carbon; The functional layer includes a first surface and a second surface along the thickness direction, and the mass content of the sp2 phase elemental carbon in the elemental carbon increases continuously or gradually from the first surface to the second surface; The mass content of sp2 phase elemental carbon in the elemental carbon on the second surface is ≥30%.
2. The wear-resistant coating according to claim 1, characterized in that: The mass content of sp2 phase elemental carbon in the elemental carbon on the first surface is ≥20%, and / or the mass content of sp2 phase elemental carbon in the elemental carbon on the second surface is ≤40%.
3. The wear-resistant coating according to claim 1, characterized in that: The functional layer is elemental carbon.
4. The wear-resistant coating according to claim 1, characterized in that: The thickness of the functional layer is 1-5 μm.
5. The wear-resistant coating according to claim 1, characterized in that: The first surface of the functional layer is adjacent to the base layer.
6. The wear-resistant coating according to claim 1, characterized in that: The mass content of the sp2 phase elemental carbon in the elemental carbon increases gradually from the first surface to the second surface.
7. The wear-resistant coating according to claim 6, characterized in that: The functional layer includes n structural layers in sequence from the first surface to the second surface, the structural layer adjacent to the first surface is the first structural layer, and the structural layer adjacent to the second surface is the nth structural layer, n≥3 and is a positive integer; the mass content of sp2 phase single carbon in each structural layer is constant; The mass of the sp2 phase single carbon of the single carbon in the nth structural layer is greater than the mass of the sp2 phase single carbon of the single carbon in the n-1th structural layer.
8. The wear-resistant coating according to claim 7, characterized in that: The functional layer includes a first structural layer, a second structural layer and a third structural layer in order from the first surface to the second surface; the mass content of sp2 phase single carbon in the first structural layer is a%; the mass content of sp2 phase single carbon in the second structural layer is b%; the mass content of sp2 phase single carbon in the third structural layer is c%; Among them, 20≤a≤25, 25<b≤35, 35<c≤40.
9. The wear-resistant coating according to claim 8, characterized in that: The thickness ratio of the first structural layer, the second structural layer, and the third structural layer is (6.5-7.5): (1.5-2.5): (0.5-1.5), or the thickness ratio of the first structural layer, the second structural layer, and the third structural layer is (3.5-4.5): (3.5-4.5): (1.5-2.5), or the thickness ratio of the first structural layer, the second structural layer, and the third structural layer is (3.5-4.5): (2.5-3.5): (2.5-3.5).
10. The wear-resistant coating according to claim 7, characterized in that: The functional layer includes a first structural layer, a second structural layer, a third structural layer, a fourth structural layer, a fifth structural layer, a sixth structural layer, and a seventh structural layer in order from the first surface to the second surface; the mass content of sp2 phase single carbon of single carbon in the first structural layer is a'%; the mass content of sp2 phase single carbon of single carbon in the second structural layer is b'%; the mass content of sp2 phase single carbon of single carbon in the third structural layer is c'%; the mass content of sp2 phase single carbon of single carbon in the fourth structural layer is d'%; the mass content of sp2 phase single carbon of single carbon in the fifth structural layer is e'%; the mass content of sp2 phase single carbon of single carbon in the sixth structural layer is f'%; the mass content of sp2 phase single carbon of single carbon in the seventh structural layer is g'%; Among them, a'=20, 20<b'≤24, 24<c'≤28, 28<d'≤31, 31<e'≤33, 33<f'≤37, 37<g'≤40.
11. The wear-resistant coating according to claim 1, characterized in that: A primer layer is also provided between the base layer and the functional layer.
12. The wear-resistant coating according to claim 11, characterized in that: The thickness of the primer layer is 50 to 1500 nm.
13. The wear-resistant coating according to claim 1, characterized in that: The base layer is composed of at least one of metal alloy, steel and alloy steel.
14. The wear-resistant coating according to claim 1, characterized in that: The Vickers hardness of the wear-resistant coating is 1130-1300 HV.
15. A method for preparing a wear-resistant coating, characterized in that: The following steps are involved: (1) Setting a base layer; (2) providing a functional layer containing elemental carbon by electrodeposition; When the functional layer is provided, the mass content of the sp2 phase elemental carbon in the functional layer is adjusted by regulating the electrodeposition bias voltage and the current.
16. The method for preparing the wear-resistant coating according to claim 15, characterized in that: The thickness of the functional layer is adjusted by the time of electrodeposition.
17. The method for preparing the wear-resistant coating according to claim 15, characterized in that: The bias voltage is set to 100-1500V.
18. The method for preparing the wear-resistant coating according to claim 15, characterized in that: When the bias voltage is set to ≤1000V, the current is set to 45-125A; when the bias voltage is set to >1000V, the current is set to 32-45A.
19. The method for preparing the wear-resistant coating according to claim 15, characterized in that: A primer layer is also arranged on the base layer.
20. A mechanical component, wherein the surface of the mechanical component or the connecting part is provided with the wear-resistant coating according to any one of claims 1 to 14 or the wear-resistant coating prepared by the preparation method of the wear-resistant coating according to any one of claims 15 to 19.